(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
This issue provides a comparative analysis of traditional and gamified methods in foreign language learning. It examines the key characteristics, advantages, and limitations of both approaches, with a special focus on modern interactive strategies such as task-based learning, CLIL, embodied learning, and inquiry-based methods. The research highlights how gamified learning increases engagement and motivation among learners, while also comparing the outdated "Army Method" with current communicative and learner-centered techniques.